2014
DOI: 10.1097/bot.0000000000000077
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Plates Overlapping Provisional External Fixator Pin Sites

Abstract: Objectives The purpose of this study was to compare the infection risk when internal fixation plates either overlap or did not overlap previous external fixator pin sites in patients with bicondylar tibial plateau fractures and pilon fractures treated with a two-staged protocol of acute spanning external fixation and later definitive internal fixation. Design Retrospective comparison study. Setting Two level I trauma centers. Patients/Participants A total of 85 OTA type 41C bicondylar tibial plateau frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 21 publications
0
21
0
3
Order By: Relevance
“…23 Recent studies, in an effort to provide objective data to find an answer, reported conflicting results. 24,25 In a small cohort comparison study, Laible and colleagues 24 did not find an increased infection rate in tibial plateau fractures fixed with plates that overlapped with pin-sites. Shah and colleagues 25 found the opposite, finding an increased infection rate with plate, pin-site overlap.…”
Section: Definitive Fixation Should Follow Soft Tissue Resolutionmentioning
confidence: 97%
See 2 more Smart Citations
“…23 Recent studies, in an effort to provide objective data to find an answer, reported conflicting results. 24,25 In a small cohort comparison study, Laible and colleagues 24 did not find an increased infection rate in tibial plateau fractures fixed with plates that overlapped with pin-sites. Shah and colleagues 25 found the opposite, finding an increased infection rate with plate, pin-site overlap.…”
Section: Definitive Fixation Should Follow Soft Tissue Resolutionmentioning
confidence: 97%
“…24,25 In a small cohort comparison study, Laible and colleagues 24 did not find an increased infection rate in tibial plateau fractures fixed with plates that overlapped with pin-sites. Shah and colleagues 25 found the opposite, finding an increased infection rate with plate, pin-site overlap. However, the authors had a more heterogeneous study cohort, including both tibial plafond and plateau fractures.…”
Section: Definitive Fixation Should Follow Soft Tissue Resolutionmentioning
confidence: 97%
See 1 more Smart Citation
“…Il rischio infettivo è infatti più alto nelle sintesi interne dopo applicazione di fissatore esterno, in particolare nelle sintesi interne con placche o chiodi posizionati nel sito di infissione delle pins. Questo fenomeno sembra anche tempo-dipendente, perché si verifica con più probabilità in fissatori posizionati da più di 2 settimane o in presenza di una secrezione dalle pin che indica un'alta probabilità di infezione [27]. Il timing e la modalità della conversione dalla fissazione esterna all'osteosintesi interna restano ancora da definire, e dipendono dalle condizioni generali del paziente, dallo stato delle parti molli, dalla persistenza dell'infezione valutata con parametri clinici, biologici e strumentali (febbre, VES, PCR, esami colturali, scintigrafia con leucociti marcati, PET-TAC, RMN).…”
Section: Stabilizzazione Della Frattura Esposta In Urgenzaunclassified
“…fino a più di 100 gg.) [27]. In casi selezionati, la persistenza di un'infezione e le condizioni generali del paziente non consentono la conversione, per cui il trattamento con fissatore esterno resta quello definitivo, con maggiore incidenza di pseudoartrosi, viziose consolidazioni e rigidità articolari, in particolar modo per le fratture del femore distale (Fig.…”
Section: Stabilizzazione Della Frattura Esposta In Urgenzaunclassified